Information Systems at the Service of the Medical-legal System in Colombia (2017)
Purpose: The article presents a reflection on the evolution and importance of information systems available to the National Institute of Legal Medicine and Forensic Sciences that support the medical-legal system in Colombia. Description: Their evolution is described from the recording of manual information in books to the introduction of the computer and the first uses of software tools as an aid for the expert service; and how information systems have become a strategic response not only for the appropriate management of the information generated by different mission processes, but also as an essential input for the administration of justice and decision-making by the State. Approach: The foregoing is based on the authors’ professional experience in engineering and information technologies governance at the Institute, based on the information and feedback received from system users and colleagues, and the interaction with authorities and consumers of institutional information. Conclusions: A projective view is proposed so that in the short and medium term the information systems supporting the medical-legal system become a source for the implementation and application of strategies and methodologies such as business intelligence, big data and data mining, among others.